Uang, Harga dan Bunga Uang - Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
Talking about money, Islam at the time of the prophet and before Islam was already familiar with currency and Islam began to print its own currency during the caliphate Umar bin Khatab. The dinars and dirhams that characterize the Muslims at that time, began to gradually disappear in the market when the Ayubbiyah dynasty came to power. Dinars and dirhams were replaced with ufulus or paper money. At that time there was a high price increase. This situation by Imaqrizi also called inflation. Because the prices of goods continue to rise due to the declining value of the currency, the demand for goods also decreases. These three conditions have brought Muslims to a global crisis that destroyed the previously built economic system. For this reason, the following will describe the relationship between money and prices at the macroeconomic level, both Islamic and conventional.